Develop an online system for 66KV sheath fault detection/location - Ahmad Waliyuddin Bin Jumat (Nanyang Technological University, 2024)
This collaborative project involves SP Group and Nanyang Technological University, focusing on detecting faults in the cable sheaths of underground cables. Regular testing of underground cables is crucial to ensure their integrity and maintain stable power transmission. However, the current process for conducting cable sheath tests is labor-intensive, costly, and time-consuming. It involves pre-checking link boxes along the cable route, which can take several days due to their numerous locations and weather conditions since the testing will be carried out outdoors. Each link box serves as a connection point between cables where the power cables meet and joint. Once the site survey for the link box locations is completed, the circuit must be shutdown before conducting the sheath test, which involves injecting a 1kV DC voltage into the cable sheath to test its withstand voltage. The testing team will then inspect each link box for anomalies detected during the insulation resistance and leakage current tests. If the sheath fails to withstand the 1kV for 1 minute, it is considered as a failed test and deemed as sheath fault is present at that specific span that was tested. This testing process can be improve as the current method only be done when the circuit has been shutdown, which in turn, limits the monitoring window to know the health of the cable sheath. Sheath fault can occur at any time without human interference. Therefore, the project aims to develop a new solution for conducting online cable sheath checks without the need for shutdown. Given the absence of existing products or ideas for an online system to detect or locate sheath faults in 66kV cables, extensive research has been undertaken in this project. The research in this project includes probing into testing methods such as acoustic and ultrasound and the devices and parts required to carry out the testing of the circuit. Further testing on site is carried out to better pinpoint the areas to be improved on the errors encountered while testing.